A comparative study of teachers' values alignment strategies in the classroom: Face-to-face versus distance education - Fatma Nur Aktaş (Journal of Pedagogical Research, 2023)
As the remarkable spread of distance education practices changes the roles of teachers and students in instructional processes, the context of classroom culture needs to be reviewed. In this revision, the importance of teachers' values alignment skills develops as conflicts between teachers' and students' values become more apparent. This case study compares values alignment strategies elementary mathematics teachers use in face-to-face and distance education. The content analysis of the data obtained using video recordings of two elementary mathematics teachers indicated that the participants' values alignment strategies were focusing, reprioritising, equilibrium, redefining, beacon, and ignoring. Face-to-face instruction often employs a strategy that considers students' values, such as the equilibrium strategy. However, in distance education, some strategies emerged in which the teacher's values are dominant, such as the beacon strategy.